Abu Limbah Sekam Padi sebagai Bioadsorben yang Efektif untuk Logam Timbal dalam Tanah - Ani Qomariyah; Ratih Hidayah (Fakultas Matematika dan Ilmu Pengetahuan Alam, 2021)
In this research, the effect of rice husk treatment, i.e. ashing to produce rice husk ash (RHA), working with base (BRH), and working with acid solution (ARH) on the adsorption capability of Pb(II) ions has been investigated. Adsorption was carried out by mixing 5 g of the adsorbent with 50 mL Pb(II) solution 100 ppm for 3 hours. The unadsorbed ions were analyzed by AAS (Atomic Absorption Spectrophotometre). Result showed that RH, RHA, BRH, and ARH adsorbents, adsorbed Pb(II) ions with the amount of 86,5 % ; 96,0 % ; 93,4 % ; and 33,0 % respectively. The highest adsorption of Pb(II) (96,0%) occured for the adsorbent of RHA. In the ashing process, the amount of heat or energy might be released and applyed as fuel in various purposes such as cooking and bricks production. Rice husk has multiple uses, besides being a fuel, it can also be used as an effective adsorbent for Pb(II) ions. The study of Pb(II) adsorption kinetics showed that a contact time of 3 hours was an effective time for rice husk ash to adsorb Pb(II) ions. The adsorption of Pb(II) metal by rice husk ash tends to follow a pseudo 2nd-order reaction kinetics pattern.